Climate change perceptions among Andean schoolchildren in Chile - Rivera, Mailing; Cortés, Wilson; Pino, Sonia; Meza, Mónica; Solis, Jaime; Merino, Cristian (Frontiers in Education, 2025)
This study explores the social representations of climate change among schoolchildren in an Andean community in northern Chile, using an ethnographic approach. Through drawings and explanations, students expressed their perspectives, revealing actionable representations that highlight their agency within the natural environment. Contrary to traditional views in scientific education, the findings underscore the importance of integrating local Andean knowledge to address environmental risks. The study involved 11 schoolchildren, aged 7–14, from a highly vulnerable rural school in Caspana, where multi-grade education is common. Data were collected through creative activities, written explanations, and group interviews, then analyzed qualitatively using semantic triangulation. The results demonstrate that Andean children perceive themselves as mediators between urban and rural worlds, capable of balancing environmental and cultural challenges. This research emphasizes the need for scientific education to value local knowledge, fostering sustainability and preserving the cultural agency of individuals in vulnerable yet environmentally significant regions.